Corporate Sponsorships of Philanthropic Activities: When Do They Impact Perception of Sponsor Brand? - Menon, Satya; Kahn, Barbara E. (Journal of Consumer Psychology, 2003)
We examined the benefits to a corporate sponsor of two types of philanthropic activities — cause promotions and advocacy advertising. Results from 4 laboratory studies indicate that perceptions of corporate social responsibility (CSR) are affected by consumers’ elaboration levels. Consumer perceptions of CSR are more favorable for cause promotions, which do not receive much elaboration, than they are for advocacy advertising, which prompts more elaboration. In addition, perceived congruence between the sponsor and the social issue is shown to moderate these effects: Higher congruence between the sponsor and social issue increases favorable ratings of CSR for cause promotions but only if elaboration on the sponsorship activity is facilitated. On the other hand, lower congruence increases favorable ratings of CSR for advocacy advertising as long as elaboration on the sponsorship is not constrained. We also found that higher congruence enhances CSR ratings if participants are primed to focus their attention on the sponsor brand, whereas lower congruence enhances CSR if participants are primed to focus their attention on the social issue.